Educational Game Development Based on Role Play Games for Students with Special Needs - Retno Purwani Sari; Iqbal Yusuf Fadillah; Riki Buldan Al Hariri; Muhammad Indra Habibi; Raiswati Untsa Mega (Universitas Negeri Padang, 2021)
The study aims to develop an educational game that can support students with special needs to learn and be experienced in life. The selection of the type of Role Play Game is expected to attract these students to participate in the learning process. To create fun learning, the Role Play Game itself provides animations, interactions, and challenges. This study applied the Luther-Sutopo method for game developments. Using this method, the developments cover game interfaces and gameplay. The results highlight interfaces and gameplay enhance game performances. They offer these students minimal difficulties in working on tasks. Therefore, this interactive and motivating game may stimulate them to learn independently. In response to current special education challenges, this educational game development has answered the demand for providing relevant learning technology for students with special needs. The gameplay of this Role-Playing Game initiates the students to learn and achieve daily living skills namely decision-making and problem solving. As one of the basic priorities of democratic societies, the principle of equal education and life opportunities operates through the use of the educational game as a learning-teaching method. This educational game development based on Role-Playing Game itself may better serve students with special needs to have better education and better life opportunities.